Cytotoxicity and genotoxicity studies of selected medicinal mushrooms extracts using Chinese hamster lung fibroblast cell line (V79) / Nur Shahirah Nasir - Nasir, Nur Shahirah (2017)
Medicinal mushrooms are well-known for nutritional benefits. However, it is necessary to evaluate the toxicity of medicinal mushrooms. The aim of this study was to identify the potential toxicity of Agaricus blazei, Grifola frondosa and Hericium erinaceus. In this study, screening of phytochemical compound, evaluating the cytotoxicity effect (MTT assay), determining the mode of cell death (Annexin V), observing the morphological changes of cell and analysing the genotoxicity (Comet Asssay) were done to assess the potential toxicity. All toxicity tests were evaluated against Chinese hamster lung fibroblast cell line (V79) using methanol and aqueous of the extracts at 0.125 mg/ml, 0.25 mg/ml, 0.5 mg/ml, 1 mg/ml and 2 mg/ml. Phytochemical screening showed the extracts contain abundantly of alkaloid. The MTT assay demonstrated that all extracts showed low cytotoxicity effect at 2 mg/ml. Only aqueous extract of A. blazei displayed the highest cytotoxicity effect at 1.7 mg/ml (IC50). The Mode of Cell Death for viable V79 cells for A. blazei was higher at 2 mg/ml (93.9% ±0.721) compared to apoptosis and necrosis using Annexin V. Cell morphology did not show any sign of apoptotic and cell injury at 1 mg/ml and 2 mg/ml of mushroom extract during 24 hours treatment. Lastly, genotoxicity activity for A. blazei, G. frondosa and H. erinaceus in V79 cell results revealed that DNA damages were detected at 1 mg/ml and 2 mg/ml. In conclusion, these three selected medicinal mushrooms had caused toxicity to normal cells as demonstrated by V79 cell line at 1 to 2 mg/ml.